2011
DOI: 10.1007/s10562-011-0619-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Alkaline Pretreated Nanoporous Gold for the CO Oxidation

Abstract: Nanoporous gold (NPG) catalysts were made by free corrosion and the effect of alkali-treatment on NPG has been investigated for the oxidation of CO. After being immersed in alkaline (NaOH or ammonia) solutions, the catalytic activity could be promoted dramatically while used for the room temperature reaction, and this promotional effect could be adjusted by varying the pH values of the alkaline solutions or immersing time. The roles of the alkaline were to provide OH -anions to form Au-OHsites, which were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In summary, the HPCN acted as a support for the cleaning and recycling of the catalyst, and the pore channels of HPCN served as a container for loading the Au NCs. As shown in Table S1 in the Supporting Information, Au/HPCN showed better catalytic performance than other traditional Au/C catalysts . The Langmuir–Hinshelwood model was applied to explain the CO oxidation mechanism occurring on the gold surface, which is shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the HPCN acted as a support for the cleaning and recycling of the catalyst, and the pore channels of HPCN served as a container for loading the Au NCs. As shown in Table S1 in the Supporting Information, Au/HPCN showed better catalytic performance than other traditional Au/C catalysts . The Langmuir–Hinshelwood model was applied to explain the CO oxidation mechanism occurring on the gold surface, which is shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Han et al 39 has found that CO conversion over NaOH (pH ¼ 12) treated nanoporous gold dropped sharply to 17% at 200 C, aer that the CO conversion increased rapidly to 100% at approximately 240 C. In other works of Au/HMS, 40 Au/MgO 41 catalyst, the CO conversion had a decreased in activity with the temperature increasing. Han et al 39 has found that CO conversion over NaOH (pH ¼ 12) treated nanoporous gold dropped sharply to 17% at 200 C, aer that the CO conversion increased rapidly to 100% at approximately 240 C. In other works of Au/HMS, 40 Au/MgO 41 catalyst, the CO conversion had a decreased in activity with the temperature increasing.…”
Section: Catalytic Activity For Co Oxidationmentioning
confidence: 95%
“…With these studies, it has been revealed that apart from silver, oxygen species such as oxidized hydrocarbon, gold oxide, and subsurface oxygen left during the leaching process play a major role in catalytic activity. 23 Han et al 24 reported an alkaline-pretreated nanoporous gold for CO oxidation ( Figure 10). AuNPore was prepared by free corrosion of Au 42 Ag 58 alloy of 25 mm thickness using nitric acid at room temperature for 24 h. After washing these AuNPore samples with ultrapure water, they were treated with alkaline solution of NaOH or ammonia for 5 or 720 min.…”
Section: Co Oxidationmentioning
confidence: 99%